DIGITAL LITERACY COMPETENCY PROFILE OF GUIDANCE AND COUNSELING TEACHER AT STATE HIGH SCHOOL IN BANDUNG - Wa Ode Husniah; Ayong Lianawati; Irvan Budhi Handaka; Irfan Fahriza; Syari Fitrah Rayaginansih; Tryanti R. Abdulrahma (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2023)
The Industrial Revolution 4.0 and Society 5.0 became one of Indonesia's educational attainment standards. The integration of technology in education is mandatory. As an integral part of education, guidance, and counseling are required to support a conducive and technology-friendly educational climate. Digital literacy is one of the competencies that must be possessed by guidance and counseling (GC) teachers. This study aims to map the distribution of GC teachers' digital literacy competencies. The respondents are 64 guidance and counseling teachers at a state high school in Bandung. Similar studies have been conducted but are not yet based on comprehensive competency standards. This study uses a quantitative approach with descriptive research methods. Data was collected through a survey using a GC teacher digital literacy self-assessment inventory. Collecting data using a questionnaire to reveal the level of digital literation, which is then analyzed conceptually and empirically from the digital literacy profile of GC teachers, using Technical Competencies for Counselor Education - The Association for Counselor Education and Supervision (ACES). Based on the study results, GC teachers' digital literacy competency profile at public high schools in Bandung City has a good trend, where GC teachers can use digital literacy to support the primary activities of the daily counseling profession. Generally, men have a higher trend in digital literacy competencies than women. In the use of social media, women have a higher tendency than men. The penetration rate of ICT implementation in counseling services is still low.